PAECILOMYCOTIC ATYPICAL MYOCARDITIS IN A CHILD - E. R. Gasparyan; A. V. Strelyaeva; I. V. Teres (Российский кардиологический журнал)
The treatment strategy was developed and monitored in a child with paecilomycotic atypical myocarditis (PAM), who was observed from the age of one to four years. The treatment included a combination of two homeopathic medications, Aconite C6 and Latrodectus mactans C6, which are permitted to use in clinical practice by the Russian Ministry of Health and Medical Industry Decree No. 335 (Supplement 2, November 29th 2005). The diet was corrected by pediatric dietologists. In one week, fever and pain syndrome disappeared; in one month, the blood levels of mycotic spherules normalized (4,500 per 1 μl). Diflucan was used as a fungicide medication. At the moment, the child’s growth and development are normal.